Comparing individual and spatial influences on foraging behaviour in Antarctic fur seals Arctocephalus gazella - Staniland, I J; Reid, K; Boyd, I L (2004)
We investigated intra-specific and geographic variation in the behaviour of female Antarctic fur seals Arctocephalus gazella by serially sampling 11 individuals throughout their breeding season using satellite tracking, time-depth recorders and radio transmitters. There was significant variation between individuals in trip durations and the maximum distance reached from the breeding beach, but not in the direction of travel. We recognised 4 categories of trip duration, depending on the location of foraging: long deep-location, long intermediate-location, short intermediate-location and short shallow-location, based on the maximum distance reached from the breeding beach and the mean depth of water where diving occurred. Trip category accounted for a greater amount of the variation between trips than the identity of the seal. Seals on long deep-location trips spent proportionally less time diving, had a lower dive rate, and dived to shallower depths for shorter durations with less bottom time than seals on short shallow-location trips. There was no significant difference in the total number of dives within trips between trip categories or between individual seals. There was also no significant difference in either the mean size of krill taken by individual seals or the incidence of fishes in their diet. These data suggest there is a strong individual component to where a seal forages especially in terms of the distance it travels from the breeding beach. However, we suggest that it is where an individual forages, not who that individual is, that determines how it will behave in terms of its diving. While individual seals may exploit areas of previous feeding success, their diving behaviour within these areas is likely to be determined by the spatial and temporal distribution of the prey within them.